2006
DOI: 10.1074/jbc.m600790200
|View full text |Cite|
|
Sign up to set email alerts
|

One Single In-frame AUG Codon Is Responsible for a Diversity of Subcellular Localizations of Glutaredoxin 2 in Saccharomyces cerevisiae

Abstract: Glutaredoxins belong to a family of small proteins with glutathione-dependent disulfide oxidoreductase activity involved in cellular defense against oxidative stress. The product of the yeast GRX2 gene is a protein that is localized both in the cytosol and mitochondria. To throw light onto the mechanism responsible for the dual subcellular distribution of Grx2 we analyzed mutant constructs containing different targeting information. By altering amino acid residues around the two in-frame translation initiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 54 publications
3
47
0
Order By: Relevance
“…This result raises the possibility that full-length Ty1 and Ty1i transcripts may utilize an internal ribosome entry site (65) upstream of AUG1 or AUG2 to drive synthesis of p22. Other mechanisms by which p22 could be translated from full-length Ty1 mRNA are leaky scanning, where scanning ribosomes sometimes initiate translation from an alternate AUG codon (66)(67)(68)(69) or translation reinitiation in which translation starts at a downstream AUG after translation of an ORF situated upstream (70,71). Although leaky scanning and translation reinitiation remain possible mechanisms, both require closely spaced AUGs.…”
Section: Discussionmentioning
confidence: 99%
“…This result raises the possibility that full-length Ty1 and Ty1i transcripts may utilize an internal ribosome entry site (65) upstream of AUG1 or AUG2 to drive synthesis of p22. Other mechanisms by which p22 could be translated from full-length Ty1 mRNA are leaky scanning, where scanning ribosomes sometimes initiate translation from an alternate AUG codon (66)(67)(68)(69) or translation reinitiation in which translation starts at a downstream AUG after translation of an ORF situated upstream (70,71). Although leaky scanning and translation reinitiation remain possible mechanisms, both require closely spaced AUGs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, alternative TISs are used to spread Grx2 antioxidant functions all over the yeast cell. (22) It was found that an alternative translation initiation was the major mechanism for the synthesis of membrane-bound and cytosolic forms of Debaryomyces hansenii 3 0 , 5 0 -bisphosphate nucleotidase also characterized by significant difference in substrate specificity. (23) Cytoplasmic and mitochondrial isoforms of Saccharomyces cerevisiae alanyl-tRNA synthetase and glycyl-tRNA synthetase are also translated from alternative TISs by leaky scanning mechanism.…”
Section: Types Of Alternative Open Reading Framesmentioning
confidence: 99%
“…S. cerevisiae contains eight GRXs (Grx1p to Grx8p), which are in different cell compartments. The dithiol GRXs Grx1p and Grx2p (CPYC active site) are mainly cytosolic, but a minor portion of Grx2p is located within mitochondria (Luikenhuis et al, 1998;Porras et al, 2006). Despite the proposed role of Grx1p and Grx2p as general thiol oxidoreductases, their absence causes only moderate hypersensitivity to superoxide (in the case of Grx1p) and to superoxide and hydroperoxide (in the case of Grx2p) (Eckers et al, 2009;Luikenhuis et al, 1998).…”
Section: Introductionmentioning
confidence: 99%